2022
DOI: 10.1021/acs.orglett.2c02590
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Selective B(4)–H Amination of o-Carboranes with Anthranils

Abstract: We report here a catalytic selective cage B4−H amination of ocarboranes employing an Ir(III) complex as a catalyst and anthranils as aminating agents, leading to a large class of B4-aminated o-carboranes with very high yields and a broad substrate scope under mild conditions without any oxidants. In these reactions, the carboxyl group serves as a traceless directing unit to determine the site selectivity and degree of substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…In point of view of the useful applications of nitrogen‐substituted carboranes in pharmaceuticals, [1] coordination chemistry, [3] and catalysis, [3d,e] we took attention in demonstrating a new synthetic method for BH amination. So far, various BH amination reactions have been reported: Redox reactions of o ‐carboranes with Na in liquid NH 3 followed by KMnO 4 treatment or Pd‐catalyzed cross‐coupling reactions of B‐iodo‐ o ‐carboranes with amides have been described to form B(3)‐N bonds (Scheme 1, a ), [7] Pd‐catalyzed B9 amination of o ‐carboranes with nitrogen sources, [8a] metal‐free direct nucleophilic B4 amination with Mg(NR 2 R 3 ) 2 , [8b] Ir‐catalyzed B3 amination of o ‐carboranes with ammonia ( b ), [8c] Rh‐ or Ir‐catalyzed B3 or B4 amination of o ‐carborane acids with sulfonamides or anilines ( c ), [8d] Ru‐ or Ir‐catalyzed B4 amination of o ‐carborane acids with sulfonyl azides ( d ), [8e,f] Pd‐catalyzed B4 amination of o ‐carborane acids with O‐benzoylhydroxylamines ( e ), [8e] and Ir‐catalyzed B4 amination of o ‐carborane acids with anthranils ( f ), [8g] Despite these various amination reactions, more effective reactions are required from various viewpoints, such as the price of the catalyst, the availability of the substrate, and the mild reaction conditions. Recently, we demonstrated Rh‐ and Ir‐catalyzed B4 amidation of o ‐carborane acids with dioxazolones [8h,i] ( g ) and mechanochemical Ir‐catalyzed B4 or B3 amidation using dioxazolones ( h and i ) [8j] .…”
Section: Methodsmentioning
confidence: 99%
“…In point of view of the useful applications of nitrogen‐substituted carboranes in pharmaceuticals, [1] coordination chemistry, [3] and catalysis, [3d,e] we took attention in demonstrating a new synthetic method for BH amination. So far, various BH amination reactions have been reported: Redox reactions of o ‐carboranes with Na in liquid NH 3 followed by KMnO 4 treatment or Pd‐catalyzed cross‐coupling reactions of B‐iodo‐ o ‐carboranes with amides have been described to form B(3)‐N bonds (Scheme 1, a ), [7] Pd‐catalyzed B9 amination of o ‐carboranes with nitrogen sources, [8a] metal‐free direct nucleophilic B4 amination with Mg(NR 2 R 3 ) 2 , [8b] Ir‐catalyzed B3 amination of o ‐carboranes with ammonia ( b ), [8c] Rh‐ or Ir‐catalyzed B3 or B4 amination of o ‐carborane acids with sulfonamides or anilines ( c ), [8d] Ru‐ or Ir‐catalyzed B4 amination of o ‐carborane acids with sulfonyl azides ( d ), [8e,f] Pd‐catalyzed B4 amination of o ‐carborane acids with O‐benzoylhydroxylamines ( e ), [8e] and Ir‐catalyzed B4 amination of o ‐carborane acids with anthranils ( f ), [8g] Despite these various amination reactions, more effective reactions are required from various viewpoints, such as the price of the catalyst, the availability of the substrate, and the mild reaction conditions. Recently, we demonstrated Rh‐ and Ir‐catalyzed B4 amidation of o ‐carborane acids with dioxazolones [8h,i] ( g ) and mechanochemical Ir‐catalyzed B4 or B3 amidation using dioxazolones ( h and i ) [8j] .…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, a −COOH directed Ir‐catalyzed cage B(4)−H amination of o ‐carboranes with anthranils was developed by Xie's group (Scheme 28), [37] in which anthranils served as the aminating reagent. In the presence of 4.0 mol% [Cp*IrCl 2 ] 2 catalyst, the reaction of carboranyl carboxylic acid 1‐COOH‐2‐R‐ o ‐C 2 B 10 H 10 with anthranils generated a variety of B(4)‐aminated carboranes in very high yields without any oxidants.…”
Section: Formation Of B−n Bondsmentioning
confidence: 99%
“…Amidation with dioxazolones was established in 2019 by Lee ( Figure 2 ,a‐ii ) [70] . In the past years, the aforementioned and other groups have developed additional protocols using {C 2 B 10 } precursors, enabling transformations such as direct B−H/N−H dehydrocoupling and regioselective B9 amination ( Figure 2 ,a‐iii and 2,a‐iv ) [71–79] . For the monocarborane cage, only one study exists regarding the B−N bond formation by B−H activation: in 2017 we identified conditions to di‐sulfonamidate this cluster, but the number of products was limited to two examples [57] .…”
Section: Introductionmentioning
confidence: 99%